Detection of Efflux pump MexX and MexY genes in Multidrug Resistant Pseudomonas aeruginosa - Ali, Kadhum Attia; Ghassan, Enass (Iraqi Journal of Science, 2024)
High antibiotic resistance among Pseudomonas aeruginosa could be viewed as the primary cause of nosocomial infections. In this study, 60 isolates of Pseudomonas aeruginosa were isolated from urine, sputum, burn, ear and wounds swab. The major goal was to determine the relationship between MexX and MexY and the resistance of MDR P. aeruginosa to many drugs. Prevalence of multidrug resistant (MDR) Pseudomonas aeruginosa was 22 isolates (36.66%) and 38 isolates (63.34%) were found to be non-MDR isolates. Moreover, molecular detection of MexX and MexY genes was done for MDR isolates.MexY gene was found in all MDR isolates and MexX gene was detected in 20 (90.9%) MDR isolates. Susceptibility test showed highly significant differences p≤0.01. Highest resistance was found against piperacillin/sulbactam (45%), followed by ceftazidime/avibactam with 33.33%, and by ceftolozane/tazobactam and levofloxacin which shared same percentage at 31.67%. Almost 23.33% were less resistant to both doripenem and colistin, and 25% to tobramycin. All these findings confirmed a positive correlation between the presence of MexX and MexY genes and an increase in the resistance for all antibiotics used in this study the results of which were highly significant at p≤0.01 for all antibiotics. The study found that some antibiotics that had not been studied previously, also had a relationship with the presence of these genes and the resistance of bacteria to antibiotics such as penicillin, unlike it was previously believed that they do not have relation with the efflux pump mechanism in P. aeruginosa and that  this bacterium use other mechanisms to resist them.